Warrior a legendary leader's dramatic life and violent death on the colonial frontier - Connors, Libby 1960- (Allen & Unwin, 2015)
Dundalli was one of the great Aboriginal warriors of the frontier, and his name is warmly remembered in the Aboriginal community of Brisbane, where he was publicly executed for murder in January 1855